Avaliação do potencial de utilização de bambu (Dendrocalamus giganteus) na produção de painéis de partículas orientadas - Miskalo, Eugênio Polistchuk (2009)
The consumption of restored wood boards has increased, bringing along the use of woods derived from reforestation, traditionally from Pinus and Eucalyptus, composed of long and short fibers respectively, which demand the enlargement and replacement of the plantation areas quickly. In this essay, the main objective was to measure the potential application of the bamboo as an alternative to make boards of Oriented Strand Board – OSB. The kind of bamboo studied was the Dendrocalamus giganteus, which is made of medium strands. Boards were produced with 4, 6 and 8% contents of phenol-formaldehyde resin. The experimental work was divided in two stages. The purpose of the first stage was to study the variation of density and the relative highness of the bamboo studied, in order to separate particles with different characteristics, and proceed the selection of the stem part with density more similar to the one indicated by MALONEY, with the purpose of making boards with similar characteristics to Pinus OSB boards, using the same production technique. On the second stage, experimental planning was applied to obtain bamboo boards of particles with two slit orientation and three numbers of adhesive. The physical and mechanical tests were performed according to the European patterns EN 300/93 and American patterns ASTM 1037-1996. The results indicated that the boards made in bamboo at the tangential direction at 6% of resin is the most appropriate to produce on a large scale, considering that its yield and mechanical behavior is comparable to commercial OSB, in agreement to quoted patterns.